Don't Wait, Innovate! Preparing Students and Lecturers in Higher Education for the Future Labor Market - Marlies Ter Beek; Iwan Wopereis; Kim Schildkamp (MDPI AG, 2022)
Technological innovations are changing our society at a rapid pace. The expansion of new technologies (e.g., tools and programs) will inevitably change future jobs in the area of, for example, engineering, healthcare, and science. People working in these areas need digital human capital, which is often acquired through education prior to starting a job. As a result, higher education systems around the globe face increasing demands to prepare their students for the changing labor market. To meet these demands, it is essential to focus on both lecturers' and students' digital competencies. Teaching professionals will have to learn to do new things using new resources. This goes beyond merely replacing work forms and resources; it is a complex process that demands a deeper way of learning in which routines and underlying knowledge and beliefs are explicitly reconsidered. Attention needs to be paid to how lecturers can gradually and continuously develop their professional competencies in the field of educational innovation with IT, to ensure these practices become embedded in future higher education. In this reflection paper, we will discuss key digital competencies for both students and lecturers. We will also focus on how lecturers develop these competencies through effective professional development (PD) activities. Based on a literature review, we present a model for effective lecturer PD with 29 'building blocks'. This model will be used to clarify practical examples of effective lecturer PD aimed at using innovative technology in higher education.